Invited Review: The spectrum of age‐related small vessel diseases: potential overlap and interactions of amyloid and nonamyloid vasculopathies. (11th September 2019) - Schreiber, S.; Wilisch‐Neumann, A.; Schreiber, F.; Assmann, A.; Scheumann, V.; Perosa, V.; Jandke, S.; Mawrin, C.; Carare, R. O.; Werring, D. J.
Abstract : Deep perforator arteriopathy (DPA) and cerebral amyloid angiopathy (CAA) are the commonest known cerebral small vessel diseases (CSVD), which cause ischaemic stroke, intracebral haemorrhage (ICH) and vascular cognitive impairment (VCI). While thus far mainly considered as separate entities, we here propose that DPA and CAA share similarities, overlap and interact, so that 'pure' DPA or CAA are extremes along a continuum of age‐related small vessel pathologies. We suggest blood‐brain barrier (BBB) breakdown, endothelial damage and impaired perivascular β‐amyloid (Aβ) drainage are hallmark common mechanisms connecting DPA and CAA. We also suggest a need for new biomarkers (e.g. high‐resolution imaging) to deepen understanding of the complex relationships between DPA and CAA.